OC-007 The National colonoscopy audit: a nationwide assessment of the quality and safety of colonoscopy in the UK. (28th May 2012) - Gavin, D; Valori, R; Anderson, J; Donnelly, M; Williams, J G; Swarbrick, E
Abstract : Introduction: Colonoscopy is the gold standard procedure for the diagnosis and non-surgical management of colonic disease. Poor quality colonoscopy is associated with complications and reduced effectiveness in disease prevention. A previous large-scale study of colonoscopy practice in the UK demonstrated disappointing results with poor caecal intubation rates and higher than expected complication rates. 1 Since then there has been significant investment in endoscopic training, a quality assurance framework for endoscopy units has been implemented and the National Bowel Cancer Screening Program has been rolled out nationally. The aim of this study was to assess the quality of contemporary UK colonoscopy. Methods: A nationwide audit of colonoscopy practice was conducted over a 2-week period from 28 February 2011 until 11 March 2011. The study was performed prospectively, with data entry occurring electronically through a purpose built website (http://www.endoaudit.com ). All units performing >100 colonoscopies annually on NHS patients were included. All colonoscopies performed on adults (>16 years of age) were included. Data on key performance indicators and complications was collected and analysed. Results: Data on 20 085 colonoscopies and 2681 colonoscopists were collected from 301 units. A validation exercise indicated that data were collected on >94% of all procedures performed nationally. The overall, unadjusted caecal intubation rate (CIR) was 92.3%. When adjusted for impassable strictures and poor bowel preparation the CIR was 95.8%. The polyp detection rate (PDR) was 32.1%. The PDR for significant polyps (>1 cm diameter) was 11.7%. 92.3% of resected polyps were retrieved. 90.2% of procedures achieved acceptable levels of patient comfort. A total of eight perforations and 52 significant haemorrhages were reported. Eight patients underwent surgery as a consequence of a complication. Conclusion: This is the first national audit of colonoscopy that has successfully captured the majority of adult colonoscopy performed during a defined time period. The data confirm that there has been a significant improvement in performance of colonoscopy in the UK since the last study reported 7 years ago (CIR 76.9%) and that performance is above the required national standards. Competing interests: None declared. Reference: 1. Bowles CJ, Leicester R, Romaya C, et al. A prospective study of colonoscopy practice in the UK today: are we adequately prepared for national colorectal cancer screening tomorrow? Gut 2004;53 :277–83.